Studi Eksperimental Karakteristik Permeabilitas Pada Arang Dan Karbon Aktif Bambu Betung - Septire Elifere, Rere; Wirawan, I Ketut Gede; Wijaksana, Hendra (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract In order to obtain a comfortable level of air in a tropical country like Indonesia, compressor-based air conditioning (AC) systems are used, which require large amounts of electricity and will exacerbate global warming. Therefore, efforts are being made to use a cooling system that is more energy efficient and environmentally friendly. The alternative cooling system is a direct evaporative cooling system. In the direct evaporative cooling system, the cooling effect is generated from the evaporation process that occurs in the pad material that has been moistened with water. The pad material itself is used as an application for the evaporative cooling system as a cooling medium. This study aims to analyze permeability characteristics of charcoal and active carbon of bamboo betung. As a raw material, bamboo can produce porous charcoal with a high specific surface area and high porosity. Carbonization temperatures of 500ºC (KB 1), 600ºC (KB 2) are used, activated carbon without holding time 500ºC (KBA 1), activated carbon without holding time 600ºC (KBA 2), activated carbon with holding time 60 minutes 500ºC (KBA 3), and activated carbon with holding time 60 minutes 600ºC (KBA 4). The results of all tests indicate that the KB 2 (600ºC) specimen has a very large potential to be used as a new pad material in the direct evaporative cooling system because it has the highest permeability results. With the following characteristics: the KB 2 specimen has a pore diameter of 8.52 ?m, has a porosity value of 17.81 % and has a permeability value of 27.98 x 10-11 cm2. Keywords: Direct evaporative cooling, bamboo betung, carbonization, carbon activation, pore structure, pore diameter, porosity, and permeability.